Improving Speaking Skill By Using Podcast At The Eleventh Grade Of SMA Negeri 5 Pematang Siantar - Tiodora Silalahi; Bismar Sibuea; Putri Ananda Aritonang (Program Studi Pendidikan Bahasa Inggris FKIP, 2023)
The aim of this research was to to analyze the effect of Using Podcast media on students’s speaking skill at the eleventh th grade of SMA Negeri 5 Pematangsiantar. in the academic year 2022/2023. This research located in medan street , Kec.Siantar Martoba, Pematangsiantar. This research used quantitative approach with true experimental design. The population in this research is the eleventh grade students at SMA Negeri 5 Pematangsiantar with total sample is 32. The data were obtained by using pretest and posttest. The data of the pretest and post- test of both groups were analyzed by using descriptive and inferential statistics (SPSS 26.0). The result of the research shows that the testing hypothesis of posttest scores was found that tcount = 18.296> ttable = 1.699 at the significance level a = 0.05 and degrees of freedom (df) = 29. So, H0 is rejected and Ha is accepted. It means that the Using of Podcast media effect significantly on student speaking skill at SMA Negeri 5 Pematangsiantar in academic year 2022/2023